2007
DOI: 10.35536/lje.2007.v12.i2.a1
|View full text |Cite
|
Sign up to set email alerts
|

Smallholders’ Access to Rural Credit: Evidence from Pakistan

Abstract: This paper presents an analysis of smallholders’ access to rural credit and the cost of borrowing using survey data from Pakistan. Rural credit in Pakistan comes from formal and various informal sources. The tenure status, family labor, literacy status, off-farm income, value of non-fixed assets and infrastructure quality are found to be the most important variables in determining access to formal credit. On the other hand, the total operated area, family labor, literacy status and off-farm income are found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 24 publications
(30 reference statements)
9
22
0
Order By: Relevance
“…Access to credit of the sampled households was analyzed using the following equation as used by several other researchers [4].…”
Section: Access To Information and Credit Sourcesmentioning
confidence: 99%
“…Access to credit of the sampled households was analyzed using the following equation as used by several other researchers [4].…”
Section: Access To Information and Credit Sourcesmentioning
confidence: 99%
“…Sarap (2000) went on to suggest that policies should be directed both towards reducing the overall transaction costs of formal loans to small farmers, and towards improved collection processes. Amjad and Hasnu (2007) found the tenure status, family labor, literacy status, off-farm income, value of non-fixed assets and infrastructure quality to be the most important variables in determining access to formal credit. They also found that the total operated area, family labor, literacy status and off-farm income are significantly related to the determination of credit status of smallholder farmers from informal sources.…”
Section: Empirical Studies On Determinants Of Access To Creditmentioning
confidence: 99%
“…This refers to the total land size cultivated by the household and it is measured in hectares (ha). It is a continuous variable and it's expected that the larger the land cultivated, the more labour required which demands more capital which can be raised through access to credit (Yehuala, 2008, Amjad andHasnu, 2007).…”
Section: Area Cultivated (Areacult)mentioning
confidence: 99%
“…ZTBL, in addition to the prevailing rate of mark-up adds several other charges like loan case file Rs.200, postal charges Rs.250 and 1 percent and 2 percent for loan up to Rs.50, 000 and above Rs.50,000 respectively as appraisal fee (Annual Report 2013, ZTBL). Amjad and Hasnu (2007) noted that the effective rate of interest was about 21 percent for the smallest landholders and about 14 percent for the largest farm-size group.…”
Section: Problems Of Existing Agricultural Creditmentioning
confidence: 99%